PENDEKATAN STRUKTURAL, EKONOMI DAN SPASIAL (ALMIRAL) SEBAGAI MODEL ALTERNATIF PENANGGULANGAN KEMISKINAN - Waluyo, Dwi Eko (Journal of Innovation in Business and Economics, 2013)
The research was conducted to develop an integrated model of poverty reduction based on spatial aspects, economic areas, structural, and administrative of East Java province. The research applied some analysis tools which include: Analysis of dominant sectors, supporting capacity analysis, Analytical Hierarchy Process (AHP), and qualitative descriptive method. The results showed that Bangkalan, Lamongan, Bojonegoro, and Batu had the highest number of very poor population due to some factors such as the low income of population, low levels of education, and poverty that were passed down by the family. Poverty reduction efforts through institutional capacity optimization has greatly intensified and running well ,yet the constraints arise from other instruments such as the adequacy of programs, activities, and funding that has not been managed properly.